Genetic Evaluation of Early Pregnancy Loss by Chromosomal Microarray Analysis: A Retrospective Analysis - Hu Ding; Honglei Duan; Xiangyu Zhu; Wei Liu; Leilei Gu; Chunxiang Zhou; Jie Li (Clinical and Experimental Obstetrics & Gynecology)
Background: Chromosomal abnormalities constitute the predominant genetic etiology of early pregnancy loss; however, conventional karyotyping analysis fails to detect submicroscopic genomic imbalances or regions of homozygosity (ROH). This retrospective cohort study utilizes chromosomal microarray analysis (CMA) to systematically investigate chromosomal abnormalities associated with early pregnancy loss. Methods: A cohort of 1006 specimens from products of conception (POCs) was collected and subjected to DNA extraction and CMA. Relevant clinical records were also reviewed. Results: Among the 1006 cases, CMA identified chromosomal abnormalities in a total of 596 cases (59.24%, 596/1006), including 529 cases (52.58%, 529/1006) with chromosomal numerical abnormalities, 58 cases (5.77%, 58/1006) with genomic imbalance, and 9 cases (0.89%, 9/1006) with ROH. The univariable analysis demonstrated that maternal age ≥35 years, paternal age ≥35 years, pregnancy loss at 8–9 weeks, and a history of live birth were significantly associated with an increased risk of numerical chromosomal abnormalities in pregnancy loss. A history of more than two pregnancy losses, pregnancy loss after 10 weeks, and conception via in vitro fertilization-embryo transfer (IVF-ET) were associated with a reduced risk of numerical chromosomal abnormalities. Multivariable regression analyses demonstrated that paternal age ≥35 years and history of live birth did not show a significant correlation. Euploid pregnancies with pathogenic or likely pathogenic copy number variations (CNVs) were not correlated with maternal or paternal age, pregnancy loss history, gestational age, IVF-ET conception, or live birth history. Conclusions: Numerical chromosomal abnormalities are the leading cause of early pregnancy loss, demonstrating significant associations with maternal age, pregnancy loss history, and gestational age. Furthermore, pathogenic or likely pathogenic genomic imbalances may contribute to euploid pregnancy loss, although the incidence of CNVs does not correlate with clinical characteristics. The potential impact of ROH on pregnancy loss warrants further investigation.